Does Mothers’ Self-Construal Contribute to Parenting Beyond Socioeconomic Status and Maternal Efficacy? an Exploratory Study of Turkish Mothers - Corapci, Feyza; Benveniste, Hande; Bilge, Sibel (Frontiers in Psychology, 2018)
This study examined the relative contribution of mothers’ self-construal to parenting above and beyond family socioeconomic status (SES) and maternal efficacy beliefs about parenting. A total of 58 Turkish mothers and their preschool-aged children participated in dyadic tasks in the laboratory setting. For the measurement of parenting, direct behavioral observations of mother–child interactions in three interaction contexts were utilized, and mother ratings of emotion socialization were obtained. Mothers also reported on their parenting efficacy, self-construal, child temperament, and family demographics. Results revealed a more balanced endorsement of autonomous and relational self-characteristics as well as more sensitive parenting among higher SES mothers. Furthermore, mothers’ self-construal contributed unique variance to the prediction of sensitive parenting over and above SES, maternal efficacy and child temperament. Yet, in the prediction of negatively controlling parenting, mothers’ self-construal did not account for unique variance. Lower parenting efficacy and lower SES were the only predictors of punishing, overriding, and distress magnifying responses. Finally, results indicated a marginally significant indirect effect from SES to sensitive parenting via autonomous-related self-construal, controlling for the indirect effect of maternal efficacy.